2018
DOI: 10.1002/anie.201805049
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Alternating Sequence for N‐Isopropylacrylamide (NIPAM) and Methacrylic Acid Units in a Copolymer by Cyclopolymerization and Transformation of the Cyclopendant Group

Abstract: An alternating copolymer of methacrylic acid and N-isopropyl acrylamide (NIPAM) was synthesized by selective cyclopolymerization of a special divinyl monomer and transformation of repeating cyclo-units in the resultant cyclopolymer. Crucial to the breakthrough is the monomer design in view of two types of cleavable bonds (3° ester and activated ester) in the pendant group of the monomer and the lower reactivity ratio of the two double bonds (methacrylate and electron-poor acrylate) for the polymerizable groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 24 publications
2
42
1
Order By: Relevance
“…Furthermore, Figure C shows the 13 C NMR spectrum of the obtained copolymer in comparison with the random copolymer, and the spectra exhibit almost identical shapes and peak‐splitting patterns. Peculiar peaks specifically due to the alternating sequence were not observed, though 13 C NMR spectroscopy of the alternating copolymer was different from random ones, and it clarified the sequence in previous works of sequence control …”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…Furthermore, Figure C shows the 13 C NMR spectrum of the obtained copolymer in comparison with the random copolymer, and the spectra exhibit almost identical shapes and peak‐splitting patterns. Peculiar peaks specifically due to the alternating sequence were not observed, though 13 C NMR spectroscopy of the alternating copolymer was different from random ones, and it clarified the sequence in previous works of sequence control …”
Section: Resultsmentioning
confidence: 56%
“…Thus, we tried to control the polymerization with various conditions of reversible deactivation radical polymerization. First, atom transfer radical polymerization (ATRP) conditions were applied to the cyclopolymerization of 1 under dilute conditions ([ 1 ] 0 =100 m m ; [initiator] 0 =2.0 m m ), which are similar to those of the cyclopolymerization of the methacrylate–acrylate divinyl monomer in our previous study . However, the conversion of the vinyl groups in 1 reached a plateau less than 50 % during the early stages of the reaction, affording low‐molecular‐weight polymers using any iron and copper catalyst in conjunction with various ligands and additives (Supporting Information, Table S1, Entries 2–9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar cooperative dehydration mechanism was reported in an aqueous solution of poly( N ‐isopropylacrylamide) (PNIPAM) based on the consecutive sequence of the NIPAM unit . Ouchi et al also reported that the thermal response of the alternating copolymers of methacrylic acid and NIPAM was less sensitive than homo PNIPAM due to the absence of a consecutive sequence of the same NIPAM unit . Indeed, polymers belonging in Group II had low sensitivity since the inserted G ‐block inhibited cooperative dehydration even though the maximum A ‐block length was only slightly reduced from DP = 15 (Group I) to 10 (Group II).…”
Section: Summary Of the Sequence‐controlled Amino‐acid‐derived Vinyl mentioning
confidence: 56%